INHERENT PROBLEMS IN ISLAM'S ENCOUNTER WITH OTHER RELIGIONS - Koovackal, George (Journal of Dharma, 1994)
Inspite of the clear cut Quranic statement that "There is no compulsion in religion (2. 256); 1 there are certain factors inherent in very fabric of Islam that make its encounter with other religions difficult and problematic. Some of its claims such as to be the religion of the whole humankind, primordial as well as the last, a panacea for all the evils of the society for all the times, to possess a scripture that has corrected, cancelled or abrogated allthe previous revelations and to have a prophet with whom prophethood has been sealed for ever etc. may not be easily accepted by the members of other religions. The wars fought by Muslims down the centuries and the fear and misconceptions regarding its rapid spread through out the world force students of history to feel that there are certain issues in inherent in Islam which force them to believe that it is impossible for Muslims to have, a positive and friendly relationship with the adherents of other religions. A brief attempt is made in the following pages to analyze those factors with some indications how to overcome them.